Study of nanomodification of nickel alloy GS3 with titanium carbide - Hlushkova, D.B.; Kalinin, A.V.; Kalinina, N.E.; Volchuk, V.M.; Saenko, V.A.; Efimenko, A.A. (Problems of Atomic Science and Technology, 2023)
The work deals with the fundamentals of nanomodification of the GS3 heat-resisting multicomponent nickel alloy, out of which blades for gas turbine engines are made. The selection of the modifier for the experimental alloy was justified; the technology of acquiring the nanomodifier, using the plasma-chemical synthesis method, was developed; and the calculations of the specific surface of the TiC particles were performed. The required quantity of nanomodifier introduced to the liquid alloy to acquire the set structure was determined experimentally. Through electronic microprobe analysis, introduction to the metal matric of nanoparticles of titanium carbide is approved. Nanomodification allows achieving refinement of the GS3 nickel alloy structure, which is going to provide an opportunity to increase the effective life of gas turbine engine blades. Розглянуто основи наномодифікування жароміцного багатокомпонентного нікелевого сплаву ЖС3, з якого виготовляються лопатки для газотурбінних двигунів. Обґрунтовано вибір модифікатора для експериментального сплаву; розроблено технологію отримання наномодифікатора за допомогою методу плазмохімічного синтезу; проведено розрахунки питомої поверхні частинок TiC. Експериментальним шляхом встановлено необхідну кількість наномодифікатора, що вводиться в розплав для отримання заданої структури. За допомогою мікрорентгеноспектрального аналізу підтверджується впровадження у металеву матрицю наночастинок карбіду титану. Наномодифікація дозволяє досягти подрібнення структури нікелевого сплаву ЖС3, що дасть можливість збільшити термін експлуатації лопаток газотурбінних двигунів.